1989
DOI: 10.1093/geronj/44.5.b118
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus Infection and Bacterial Clearance in Young Adult and Aged Mice

Abstract: The effects of influenza A/Hong Kong/68 (H3N2) virus infection on clearance of bacteria (Staphylococcus aureus or Serratia marcescens) from lungs of young adult (8-week-old) and aged (2-year-old) CBA/2N mice were studied. No consistent differences in pulmonary bacterial clearance were observed in uninfected animals of either age group. However, both young and aged virus-infected mice consistently exhibited significantly reduced ability to clear challenge bacteria from their lungs compared to age-matched nonvir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The present findings are consistent with previous reports demonstrating no differences in bacterial clearance between otherwise healthy young and aged mice (Wyde et al, 1989). Conversely, bacterial clearance deficits have been reported in aged rats, but it is important to note that in these cases, the endotoxin dose was extremely high (approximately one order of magnitude or more higher than in our model), and caused 100% mortality (Horan et al, 1991).…”
Section: Discussionsupporting
confidence: 94%
“…The present findings are consistent with previous reports demonstrating no differences in bacterial clearance between otherwise healthy young and aged mice (Wyde et al, 1989). Conversely, bacterial clearance deficits have been reported in aged rats, but it is important to note that in these cases, the endotoxin dose was extremely high (approximately one order of magnitude or more higher than in our model), and caused 100% mortality (Horan et al, 1991).…”
Section: Discussionsupporting
confidence: 94%
“…Viral induced immunosuppression can allow for a bacterial super infection, as host immune responses can be suppressed when immunologic cells are impaired during influenza infection and immune cell dysfunction can reduce the host’s ability to fight bacteria (Peltola and McCullers, 2004; Brundage, 2006; Wu et al, 2011). Many studies involving animal models have shown that influenza infection increases and prolongs bacterial growth, due to reduced macrophage accumulation and decreased bacterial clearance due to reduced phagocytic activity (Kleinerman et al, 1976; Wyde et al, 1989; Sun and Metzger, 2008). Additionally it has recently been shown that S. pneumoniae and influenza co-infection results in a reduction in the number of local alveolar macrophages, this due to increased death of these macrophages by apoptosis and necrosis (Sharma-Chawla et al, 2016).…”
Section: Factors Affecting the Severity Of Bacterial Co/secondary Infmentioning
confidence: 99%
“…Staphylococcus aureus, Staphylococcus pneumoniae and Haemophilus influenza are the most common pathogens involved in influenza-associated bacterial pneumonia. The increased susceptibility to secondary bacterial invasion following influenza infection is attributed to decreased mucociliary clearance by the airways, enhanced bacterial adherence to influenza-infected cells, immunosuppression caused by virus infection, and decreased bacterial clearance by phagocytes (Rouse & Horohov, 1986;Wyde et al 1989;Leigh et al 1991). On the other hand, S. aureus has been shown to secrete a protease capable of activating haemagglutinin by proteolytic cleavage in vitro.…”
Section: Effects Of Influenza Infection On the Hostmentioning
confidence: 99%